2020
DOI: 10.5194/hess-24-417-2020
|View full text |Cite
|
Sign up to set email alerts
|

On the role of operational dynamics in biogeochemical efficiency of a soil aquifer treatment system

Abstract: Abstract. Sustainable irrigation with treated wastewater (TWW) is a promising solution for water scarcity in arid and semi-arid regions. Soil aquifer treatment (SAT) provides a solution for both the need for tertiary treatment and seasonal storage of wastewater. Stresses over land use and the need to control the obtained water quality makes the optimization of SAT of great importance. This study looks into the influence of SAT systems' operational dynamics (i.e., flooding and drying periods) as well as some as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 24 publications
3
34
0
Order By: Relevance
“…For example, in our system, DPs of >240 min did not pose a significant advantage in terms of nitrification rates or DOC degradation, mainly since in the longer DPs, most of the DOC and NH + 4 were consumed in the upper few centimeters of the profile. However, one of the major benefits of implementing long DPs has been shown to be related to improved aeration of the deeper parts of the vadose zone and extension of the aerobically active part of the soil profile (Ben Moshe et al, 2020). Hence, operating the same SAT system with higher organic load inflow solution at different DPs should theoretically result in a notable difference in degradation efficiency between shorter and longer DPs.…”
Section: Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in our system, DPs of >240 min did not pose a significant advantage in terms of nitrification rates or DOC degradation, mainly since in the longer DPs, most of the DOC and NH + 4 were consumed in the upper few centimeters of the profile. However, one of the major benefits of implementing long DPs has been shown to be related to improved aeration of the deeper parts of the vadose zone and extension of the aerobically active part of the soil profile (Ben Moshe et al, 2020). Hence, operating the same SAT system with higher organic load inflow solution at different DPs should theoretically result in a notable difference in degradation efficiency between shorter and longer DPs.…”
Section: Scenariosmentioning
confidence: 99%
“…Since SAT systems are usually operated in cycles of flooding and drying, dissolved oxygen (DO) concentrations and redox conditions depend on the system's hydraulic operation. In a medium-scale laboratory setup implementing flooding and drying cycles, the advantage of long drying periods (DPs) for deep aeration was demonstrated (Ben Moshe et al, 2020). The objective of this study is to further investigate this idea by the development of a model that will enable to simulate and assess different scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…In the Shafdan SAT, the secondary WW effluent infiltrates into the coastal aquifer through a 25-35-m sandy unsaturated system [21]. However, increasing WW volumes and escalating real estate prices around urban areas highlight the need to re-engineer the SAT process and maximize the recharge capacity without sacrificing the effluent quality [22]. Therefore, efforts are being made to maximize the percolation flux by: (1) Studying the spatiotemporal infiltration dynamics across the ponds using hydro-geophysical tools [23]; (2) releasing air which is entrapped below the wetting front [24]; (3) improving tillage technologies to effectively break the biocrust and maintain high infiltration rates in the ponds [25]; and (4) improving the SAT management by optimizing the length of the wetting and drying cycles.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal ratio of HLCs during SAT is very site-specific, though it was shown that the wet-dry ratio should be smaller than one to keep the system efficient in pollutant removal [29]. A higher HLC frequency with shorter flooding cycles is advantageous for organic compound removal during SAT [30,31]. Compared to continuous infiltration, cyclic infiltration shows better degradation rates for compounds such as diclofenac [32].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to continuous infiltration, cyclic infiltration shows better degradation rates for compounds such as diclofenac [32]. Nevertheless, SAT design is still advised with flooding cycles of 1-3 days [33], even though a higher frequency of HLCs with shorter cycle phases has shown better performance for water quality improvement due to increased topsoil aerating [30,31]. The drying phase leads to an aeration of the vadose zone.…”
Section: Introductionmentioning
confidence: 99%